A Mixed-Method Analysis of Posttrauma Outcomes: Trauma Severity and Social Support from a Psychotherapeutic Perspective - Rieck, Murray; Shakespeare-Finch, Jane; Morris, Bronwyn; Newbery, Jasmin (Canadian Journal of Counselling and Psychotherapy, 2007)
While research has focused on the difficulties faced in adapting to life following the experiences of a traumatic event, limited research has examined positive legacies of incorporating a traumatic experience into life posttrauma. This study uses quantitative and qualitative data (N = 218) to examine the effect that trauma severity and social support have on posttrauma outcomes. Individuals’ perceptions of their traumatic experiences and the social support they received were significant influences posttrauma. The knowledge gained has practical applications for therapy and the client/counsellor relationship in terms of counselling and facilitating personal growth after trauma.